Clinical Effects of Chlorhexidine 0.2% and Cetylpyridinium 0.05% Combination in Comparison with Chlorhexidine, Cetylpyridinium and Persica in Reducing Oral Bacteria in Healthy Individuals - Nioosha Yarahmadi; Farshad Hashemian; Reza Hosseini Doust (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background:  Preparation of a new product with the goal of reducing chlorhexidine's side effects without decreasing (and even increasing) its effectiveness is a desirable goal for researchers in the field of oral hygiene. The aim of this study was to evaluate the efficacy of Chlorhexidine 0.2% and Cetylpyridinium 0.05% combination in reducing oral bacteria in comparison with Chlorhexidine 0.2%, Cetylpyridinium 0.05% and Persica mouthwashes. Methods: 100 healthy volunteers aged between 18 and 30 years were randomly assigned to 5 groups. The first group received Chlorhexidine 0.2%, the second group received Cetylpyridinium 0.05%, the third received Persica, the fourth received Chlorhexidine 0.2% plus Cetylpyridinium 0.05%, and the fifth group received Chlorhexidine 0.05% plus Cetylpyridinium 0.05%. Samples were obtained at baseline and thirty minutes after oral rinsing with the mouthwashes. The number of colony-forming units (CFU/mL) before and after mouthwash administration was compared for each sample.   Results: The preparation with the most bacterial count reduction was found to be Chlorhexidine 0.2% and Cetylpyridinium 0.05% combination. However, the difference between efficacy of Chlorhexidine 0.2% plus Cetylpyridinium 0.05% and Chlorhexidine 0.05% plus Cetylpyridinium 0.05% was found not to be statistically significant.                                                        Conclusions: A new mouthwash preparation including chlorhexidine 0.05% and cetylpyridinium 0.05 % combination is the most desirable due to the increased efficacy and fewer side effects.